Integrasi Kearifan Lokal Sedekah Bumi dalam Pencapaian P5 di Sekolah Dasar - Siti Aisyah; Muhammad Faizi Adiyatna; Anisatuzzahra Anisatuzzahra; Muhammad Nofan Zulfahmi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Local wisdom plays an important role in education, especially in shaping students' characters in accordance with the nation's cultural values. This study aims to examine the integration of local wisdom Sedekah Bumi in achieving the Pancasila Student Profile (P5) in elementary schools. Sedekah Bumi, as a local tradition rich in cultural values, can be an effective medium in shaping students' characters in accordance with Pancasila values. The research method used is literature study and qualitative research with a descriptive approach. The results of the study indicate that the integration of Sedekah Bumi in the elementary school curriculum can improve students' understanding of Pancasila values, such as mutual cooperation, social concern, and love for the environment. This implementation also supports the achievement of P5 which includes believing and being devoted to God Almighty, global diversity, mutual cooperation, independence, critical thinking, and creativity.